2015
DOI: 10.1371/journal.pone.0142139
|View full text |Cite|
|
Sign up to set email alerts
|

A Tandem Oligonucleotide Approach for SNP-Selective RNA Degradation Using Modified Antisense Oligonucleotides

Abstract: Antisense oligonucleotides have been studied for many years as a tool for gene silencing. One of the most difficult cases of selective RNA silencing involves the alleles of single nucleotide polymorphisms, in which the allele sequence is differentiated by a single nucleotide. A new approach to improve the performance of allele selectivity for antisense oligonucleotides is proposed. It is based on the simultaneous application of two oligonucleotides. One is complementary to the mutated form of the targeted RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These observations reflect the incorporation of modified nucleotides into the TFO strand. In addition, the number and position of LNA and 2-thioU nucleotides affect the biological potential of TFOs 48 . Despite the lack of direct correlation between the binding affinities of TFOs and their GFP gene silencing, simultaneous incorporation of the two modifications (LNA and 2-thioU) into TFO strand is beneficial for triplex formation.…”
Section: Resultsmentioning
confidence: 99%
“…These observations reflect the incorporation of modified nucleotides into the TFO strand. In addition, the number and position of LNA and 2-thioU nucleotides affect the biological potential of TFOs 48 . Despite the lack of direct correlation between the binding affinities of TFOs and their GFP gene silencing, simultaneous incorporation of the two modifications (LNA and 2-thioU) into TFO strand is beneficial for triplex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Given the RNA-antisense oligonucleotide interactions, in this SNP, a destabilizing A-dC single mismatch occurs in the duplex of the WT RNA-mutant-complementary gapmer eKM. Due to the mismatch, binding of the eKM gapmer to WT RNA 693 (A allele) is about two times weaker than to the complementary mutant RNA (G allele) 26 . However, the central position of this mismatch type did not influence RNase HI selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting SNPs by ASOs to distinguish between wild type and mutant alleles is based on the occurrence of a single mismatch in one of the two RNA/ASO duplexes. Differentiation between the cleavage rates of these duplexes by RNase H might vary depending on the mismatch type and position with the ASO/target RNA duplex 26 . Single mismatch discrimination cleavage of a target RNA with RNase H was reported by Giles et al ., who used chimeric methylphosphonodiester/phosphodiester oligonucleotides 27 .…”
Section: Introductionmentioning
confidence: 99%
“…,b; Magner et al . ). In 2013, Evers and colleagues showed that an oligonucleotide‐mediated exon skipping strategy targeting the polyQ repeat did not impact ataxin‐3 molecular function, and the new truncated protein did not display any toxicity in vivo (Evers et al .…”
Section: Therapeutic Perspectivesmentioning
confidence: 97%